Ten‐year observational follow‐up of PROactive: a randomized cardiovascular outcomes trial evaluating pioglitazone in type 2 diabetes. Issue 3 (8th January 2016) - Erdmann, E.; Harding, S.; Lam, H.; Perez, A.
Abstract : Aims: To conduct a 10‐year, observational follow‐up of patients completing PROactive to investigate whether trends of cardiovascular benefit with pioglitazone and imbalances in specific malignancies persisted over time. Methods: Macrovascular endpoints and malignancies were compared based on original randomization to pioglitazone or placebo and 'any' versus 'no' pioglitazone use for bladder and prostate cancer. Results: Of 4873 patients completing the PROactive trial, 74% entered the follow‐up. During follow‐up (mean 7.8 years), there were no statistically significant differences in the primary [all‐cause mortality, myocardial infarction (MI), cardiac intervention, stroke, major leg amputation, leg revascularization] or main secondary (death, MI, stroke) endpoints for subjects originally randomized to pioglitazone and placebo, except for leg amputations during follow‐up [4.1% pioglitazone, 5.6% placebo; hazard ratio 0.74, 95% confidence interval (CI) 0.55–0.99; p = 0.046]. During follow‐up, the incidence of total malignancies was similar between groups; bladder cancer was reported in 0.8% of patients (n = 14) in the pioglitazone versus 1.2% (n = 21) in the placebo group [relative risk (RR) 0.65, 95% CI 0.33–1.28], and prostate cancer was reported in 44 men (3.7%) in the pioglitazone versus 29 men (2.5%) in the placebo group (RR 1.47, 95% CI 0.93–2.34). Conclusions: The trends of macrovascular benefits of pioglitazone compared with placebo during PROactive did not persist in the absence of continued pioglitazone during this 10‐year follow‐up. Trends of decreased bladder cancer and increased prostate cancer were observed in the pioglitazone group during follow‐up; however, these imbalances should be interpreted with caution because of the limitations of the observational study design.